2018
DOI: 10.1002/slct.201702969
|View full text |Cite
|
Sign up to set email alerts
|

Aerosil‐Supported Ionic‐Liquid‐Phase (ASILP) Mediated Synthesis of 2‐Substituted Benzimidazole Derivatives as AChE Inhibitors

Abstract: Aerosil supported ionic liquid phase (ASILP) has been prepared by confinement of ionic liquid [Bmim]PF6 on the aerosil support by adsorption interactions. This novel ASILP served as robust heterogeneous catalyst in the synthesis of biologically relevant 2‐substituted benzimidazoles from o‐phenylenediamines and aryl aldehydes in high yields under mild reaction conditions. The molecular docking studies revealed potential of 2‐substituted benzimidazoles to act as acetyl cholinesterase inhibitors (AChE).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…In 2018, a team of researchers led by Sonawane [53] made a significant contribution to the field of organic chemistry by developing a novel method for synthesizing pyrano[2,3‐ d ] pyrimidinediones, a class of organic compounds denoted as 18 in their study. The method they developed is characterized by its use of zirconocene dichloride (Cp 2 ZrCl 2 ) as a catalyst.…”
Section: Synthetic Techniques For the Preparation Of Pyrano[23‐d]pyri...mentioning
confidence: 99%
“…In 2018, a team of researchers led by Sonawane [53] made a significant contribution to the field of organic chemistry by developing a novel method for synthesizing pyrano[2,3‐ d ] pyrimidinediones, a class of organic compounds denoted as 18 in their study. The method they developed is characterized by its use of zirconocene dichloride (Cp 2 ZrCl 2 ) as a catalyst.…”
Section: Synthetic Techniques For the Preparation Of Pyrano[23‐d]pyri...mentioning
confidence: 99%
“…The imidazolium liquids are among the most popular ionic liquids applied in the SILP systems, and this brings about continuous improvement in the systems in which they are employed. An example is a new system with the use of [BMIM]PF 6 and pyrogenic amorphous Aerosil silica, which was applied as a catalyst for the synthesis of benzimidazole-the compound that has fungicidal properties [76].…”
Section: Supported Ionic Liquid Phase Catalysts (Silpcs)mentioning
confidence: 99%
“…Also, the prepared benzimidazoles revealed good antifungal activity against Candida albicans (NCIM-3466) and Aspergiillus niger (NCIM-3495). Additionally, molecular docking studies of synthesized benzimidazoles revealed hydrogen bonding interactions with receptor enzyme of acetylcholinesterase (AChE) and so prepared benzimidazoles act as inhibitors for AChE [39].…”
Section: Scheme-14: Reaction For the Synthesis Of 2-phenyl-1h-benzimimentioning
confidence: 99%